Towards A Greener Future: Assessing The Sdg’s Contributions Of Leading Chemical Companies (Journal of Namibian Studies : History Politics Culture, 2023)
This research examines the environmental sustainability practices of five leading chemical companies—Reliance Industries, Pidilite Industries, SRF Ltd., P I Industries, and Deepak Nitrite. The study aims to evaluate their contributions to the Sustainable Development Goals (SDGs), compare their sustainability efforts, and provide recommendations for future enhancements. By analyzing data from annual reports, sustainability disclosures, ESG ratings, and other credible sources, the research assesses each company’s alignment with global sustainability objectives, effectiveness in mitigating environmental impacts, and innovation in sustainable practices.